Adaptação acadêmica e saúde mental: uma análise do hardiness em estudantes universitários submetidos a diferentes metodologias de ensino - Santos, Jéssica July Dantas (2023)
The present dissertation sought to analyze the relationship between the characteristics of the hardiness personality and mental health in academic environments that use different teaching methodologies. For this, three studies were carried out. In Study 1, a narrative review of the literature was carried out on the hardiness construct and its mitigating potential in relation to the effects of stress in the face of adverse events that require adaptation. The results of study 1 identified the relevance of the hardiness personality profile as an element capable of mitigating the effects of stress and improving the ability of university students to deal with adverse situations. Study 2 consisted of a document analysis study with the objective of identifying the main categories of academic stressors reported by students of active teaching methodologies who sought psychological support at the Federal University of Sergipe between 2014 and 2021, at the Campus Professor Antônio Garcia Filho. It was found that female students, from the physiotherapy course and from the first cycles, constitute the profile with the greatest search for psychological care. The interpersonal category was the one that obtained the most reports among the stressors and the complaint most reported by the students was anxious symptoms. Finally, in Study 3, an explanatory model for anxiety and depressive symptoms was tested, with hardiness as a predictor variable and academic adaptation as a mediating variable in academic contexts with different teaching methodologies and students in the health area. It was found that the explanatory model for anxiety and depression in the academic context was satisfactory and there was no difference between the variables by campus. It is believed that these studies can bring important data about the efficiency of hardiness as an adjustment factor in the face of the stressor event of academic adaptation. As well as its protective aspect in relation to the negative impacts, at a mental and academic level, resulting from this stressful situation.